PERILAKU PETANI DALAM PENGALOKASIAN SUMBERDAYA UNTUK MENCAPAI PENDAPATAN MAKSIMUM DI KECAMATAN SIGI BIROMARU KABUPATEN DONGGALA (Suatu Analisis Linear Programming) - ANTARA, MADE (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 4, No. 3 November2004, 2012)
The conversion in the use of rice land to non-agriculture purposes in Sigi Biromaru District increased each year. One initiative of government to increase production in limited land is intensification and diversification of agriculture. In spite of, the program application is not evenly distributed in the field. So that, the farmer activity on allocating resources optimally has not been achieved that they did not obtaine a maximum income. The research is aimed: (1) to study a rational of the farmer in a allocating resources, (2) to study a resources optimal allocation, and (3) to observe the respond from a resources optimal allocation of the farmer household, if there is economic and technical efficiency changes in the agriculture enterprises. Based on the data analysis, it can be concluded that: (1) the farmer in rural village of Pakuli is more rational than farmer in urban village of Jono Oge village, (2) Although both sampled villages have the same resources optimal allocation, but productivity of resources was achieved by farmers in Pakuli higher than farmers in Jono Oge village, (3) maximum income was achieved, if simultaneous changes is made in technical efficiency , credit ceiling and form products sold (in hulled rice) to encounter input and output price fluctuation.
Keywords: Resources Allocation, Maximum Income, Linear Programming